Pendekatan Holistik Pada Pria Usia 52 Tahun Dengan Tinea Cruris Melalui Pendekatan Kedokteran Keluarga di Puskesmas Rawat Inap Tanjung Sari - Shoafa Marwah; Reni Zuraida (Medula, 2023)
In Indonesia, dermatophytosis is 52% of all dermatomycosis and Tinea Cruris is the most common dermatophytosis. This disease is important to be managed comprehensively so that treatment goals can be achieved. Family doctor practice are evidence based medicine by identifying risk factors, clinical problems, and patient management based on patient problems with a patient centered and family approach. This study is a case report. Primary data were obtained through history taking, physical examination, labs exam and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning to the end. Before intervention, the patient's knowledge about the disease and personal hygiene was lacking. The family's knowledge of Tinea Cruris is still low. After the intervention, there was an improvement in the knowledge score of patients and their families which increased by 50 points. A holistic management has been carried out with the approach of a family doctor, Mr. I was 52 years old with Tinea Cruris based on initial holistic diagnostics. The interventions carried out have increased patient knowledge and changed some of the behavior of patients and their families, as indicated by improvements in the final holistic diagnostic